Framework for MPLS-based control of optical SDH - Bernstein, G. (IEEE Network : the magazine of global information exchange)
The suite of protocols that defines multiprotocol label switching is in the process of enhancement to generalize its applicability to the control of optical networks. One area of prime consideration is to use these generalized MPLS protocols in upgrading the control plane of optical transport networks. This article describes those extensions to MPLS directed toward controlling SDH/SONET networks. SDH/SONET networks are ideal candidates for this process since they possess a rich multiplex structure, and a variety of protection/restoration options are well defined and widely deployed. We discuss the extensions to MPLS routing protocols to disseminate information needed for transport path computation and network operations and the extensions to MPLS label distribution protocols needed for provisioning of transport circuits